Linear complexity of binary sequences with interleaved structure. Issue 15 (1st October 2013) - Xiong, Hai; Qu, Longjiang; Li, Chao; Fu, Shaojing
Abstract : In this study, the minimal polynomials and the linear complexity of interleaved binary sequences are investigated. Both the linear complexity and the minimal polynomials of low correlation zone sequences constructed by Zhou et al. are completely determined. Besides, an open problem proposed by Li and Tang is discussed. At last, a sufficient condition and a necessary condition are presented about when the linear complexity of the interleaved sequences constructed by Tang et al. attains the maximum.